DESIGN AND PERFORMANCE ANALYSIS OF 28 GHZ MIMO ANTENNA FOR 5G COMMUNICATIONS - Irfan Ali,; Malik Shehram Khan,; Bilal Ur Rehman,; Kifayat Ullah,; Humayun Shahid,; Jin Zhu, (Spectrum of Engineering Sciences, 2025)
This research examines the specifications of the 5G mobile communication network. The arrangement distinctly illustrates the two conventional semi-circular microstrip patches of the MIMO antennas operating at 28 GHz. The antenna employs embedded feeding technology, with Rogers RT/duroid 5880 as the dielectric substrate. The antenna dimensions are 18mm x 36mm x 0.8mm. The Defected Ground Structure (DGS) is groove-deflected on the ground plane to enhance impedance bandwidth and optimize isolation performance; therefore, the impedance-matching bandwidth is 5.6 GHz, substantially augmenting the antenna's frequency flexibility. Furthermore, the design incorporates a T-shaped slot in the chosen optimization, mitigating electromagnetic interference among the antenna parts. The test findings indicate that the antenna will exhibit a reflection coefficient (S11) below -10 dB within the frequency range of 24.9 GHz to 30.5 GHz, and the mutual coupling (S21) will be below -40 dB. The Envelope Correlation Coefficient (ECC) is below 0.005, the radiation efficiency is above 95, and the diversity gain (DG) surpasses 9.99 dB, therefore fully satisfying the performance criteria for 5G communication systems. The MIMO arrangement minimizes return loss and broadens operational bandwidth. Consequently, it results in tasks characterized by minimum mutual coupling, thereby substantially improving the major performance parameters of directivity, gain, and radiation efficiency.